The Variation Law of CO2 Adsorption / Desorption Energy of Coal under Infrared Action - Ma, Kai (E3S web of conferences, 2024)
The adsorption / desorption process of coalbed methane is actually a process of mutual transformation between free state and adsorbed state of gas molecules. Because the molecular movement process is inevitably accompanied by energy changes, it is of great significance to study the energy changes in the process of CO2 adsorption / desorption of coal to study the migration law of coalbed methane. The adsorption and desorption characteristics of CO2 on coal under different infrared powers were studied by using the self-designed infrared isothermal adsorption / desorption simulation tester. The energy calculation theory in the adsorption / desorption process was used to obtain the energy change law in the adsorption / desorption process under the experimental conditions. The results show that the CO2 adsorption / desorption efficiency of coal under the action of power infrared can be explained from the energy point of view, and the free energy of the adsorption and desorption state is affected by the infrared power and pressure, which is consistent with the experimental results of CO2 adsorption / desorption of coal under the action of power infrared. The adsorption characteristic curves of different infrared powers have basically the same change trend, which all meet the cubic polynomial fitting relationship, and the fitting degree is high, R2 is above.